Respuesta :

Answer:

No real solutions

129

Step-by-step explanation:

The quadratic formula is

-b ± sqrt(b^2 -4ac)

----------------------------

2a


3x^2 =2x-1

Lets get the equation in proper form

3x^2 -2x+1 = 2x-1-2x+1

3x^2 -2x+1 =0

a=3  b=-2 c=1

Lets substitute what we know

2 ± sqrt((-2)^2 -4(3)(1))

----------------------------

2(2)

-2 ± sqrt(4-12)

----------------------------

2(2)


-2 ± sqrt(-8)

----------------------------

4


No real solutions


The quadratic formula is

-b ± sqrt(b^2 -4ac)

----------------------------

2a


2x^2 -10= 7x

Lets get the equation in proper form

2x^2 -7x-10 = 7-7x

2x^2 -7x-10 =0

a=2  b=-7 c=-10

Lets substitute what we know, we are only looking for what is inside the radical

(b^2 -4ac)

((-7)^2 -4(2)(-10))

(49 +80)

129

Otras preguntas

ACCESS MORE